Evaluation of Anti-Cancer, Pro-Apoptotic, and Anti-Metastatic Effects of Synthetic Analogue Compound 2-Imino-7-Methoxy-4-(4-fluorophenyl)-2H-1,3-Thiazino [3,2-a] Benzimidazole on Pancreatic PaCa-2 and Melanoma A375 Cancer Cells - Mpho Ndou; Marthe C. D. Fotsing; Michael H. K. Kengne; Edwin M. Mmutlane; Derek T. Ndinteh; Mthokozisi B.C. Simelane; Lesetja Motadi; Mpho Choene (Acta Medica Iranica)
Synthetic compounds are widely used in cancer drug discovery. Chemotherapies aim to inhibit proliferation and induce apoptosis however, they have limitations. This study aims to explore in vitro anti-proliferative, pro-apoptotic, and anti-metastatic effects of 2-imino-7-methoxy-4-(4-fluorophenyl)-2h-1,3-thiazine [3,2-a] benzimidazole against pancreatic and melanoma cancer cell lines. Cell viability assays were conducted using Alamar blue assay. Caspase 3/7 activation was evaluated using caspase-Glo® 3/7 substrate reagent. Gene expression was analyzed using conventional polymerase chain reaction (PCR). Cell migration was assessed using wound healing. Alamar blue assay showed that the molecule studied exhibited antiproliferative activity on both the PaCa-2 and A375 cell lines, however, with higher cytotoxicity on PaCa-2 which suggests that it is cell-line dependent. Caspase 3/7 activity was upregulated in PaCa-2 and downregulated in A375, suggesting caspase-dependent and caspase-independent cell death, respectively. p53 and Bax were upregulated on both cell lines which suggests that the compound might have induced apoptosis and autophagy. Wound healing showed a decreased cell migration on both cell lines an important stage of metastasis. The study suggests that the study molecule can be a promising chemotherapeutic agent in the development of new anticancer drugs.